Norwid i Kierkegaard — czy spotkanie było możliwe? - Lijewska, Elżbieta (My University, 2011)
This article considers a possibility of an experience of a literary liaison between Cyprian Norwid’s literary output and the thought of Søren Kierkegaard. A certain coincidental similarity of some of the ideas represented in both authors’ works is, in fact, intriguing and thoughtprovoking. Another relevant element is the name of the protagonist Quidam that appears in both authors. Tough it cannot be proved conclusively that the Polish poet did know the works of Kierkegaard, who had earned himself an eloquent nickname of the Socrates of Copenhagen, there are premises to believe that Norwid could have been aware of some of the facts concerning the Danish philosopher. The author of the article supports this assumption by providing some interesting data of particular circumstances and particular persons that suggest that the above was possible. The article discusses some of the possible tangential points shared by both thinkers: 1) widespread interest in Scandinavia in the then Europe, 2) anti-Hegelian criticism in Berlin, and 3) pursuit of religious revivalism among Protestants and Catholics alike. The article indicates the people within Norwid’s inner social circle that could have been some sources of information on the Danish philosopher.
Norwid and Kierkegaard — was an encounter possible?
Keywords: Cyprian Norwid; Søren Kierkagaard; danish-polish contacts; anti-Hegelian criticism; Berlin-based Polish diaspora in the 19th c.